A cross-cultural research experience: developing an appropriate methodology that respectfully incorporates both Indigenous and non-Indigenous knowledge systems. Issue 5 (8th April 2016) - Goulding, Dorothy; Steels, Brian; McGarty, Craig
ABSTRACT: This paper engages with the methodology being used within a research project auditing concerns and aspirations in an impoverished Indigenous community in North West Australia. The community is in the heart of booming resource industries and it symbolizes the many challenges and opportunities for contemporary Australia. The paper advances the notion that social scientific research with Indigenous communities can be positioned not just as the result of consultation with the communities but as the authorized product of those communities. Although this adds to the complexity of the governing forces that impact on researchers, it also affords new possibilities for meaningful social change. If research starts with the proposition that social scientific research with Indigenous communities can be about what communities want to know, and finding out what they have to say, we may make more progress than by asking what needs to be done.